Hepatitis B in symptomless Danish homosexual men. Issue 1 (February 1988) - Munck, L K; Petersen, C S; Bech, K; Thomsen, A C; Kroon, S; Worm, A M; Wantzin, G L; Gerstoft, J
Abstract : Forty eight symptomless homosexual men attending a sexually transmitted disease (STD) clinic and found by screening to have hepatitis B surface antigen (HBsAg) were followed up for a median of 10 (range six to 26) months to characterise their liver disease. Initially 33/50 (66%) of the men had increased serum liver enzyme activity and 19/47 (40%) had increased serum immunoglobulin G concentrations. Liver biopsy specimens showed acute hepatitis B in 12 (39%) and chronic hepatitis B in 19 (61%) of the 31 patients who underwent liver biopsy. The course of the infection was: acute hepatitis B in 14/48 (29%), chronic persistent hepatitis B in 23/48 (48%), chronic aggressive hepatitis B in 8/48 (17%), and cirrhosis in 3/48 (6%) of the patients. Antibodies against human immunodeficiency virus (HIV) were present in 16/45 (36%) of the patients, but the presence of antibodies to HIV did not influence the course of hepatitis B in the observation period.